Association of Pure Tone Audiometry with DPOAE in Students after Shooting Practice at East Java State Police Academy, Mojokerto, Indonesia - Mochammad Ridwan Indiyana1 , H.M.S. Wiyadi2 , Artono3 , Nyilo Purnami4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Analyzing the association between pure tone audiometry and distortion of otoacoustic emission(DPOAE) in students after shooting practice.Methods: This study was conducted at the East Java State Police Academy, Mojokerto, Indonesia, fromAugust 2018 to January 2019. Participants were examined for pure tone audiometry and DPOAE two weeksafter shooting training. Participants previously had undergone shooting training for 5 months, with scheduleof 4 times per week. The statistical test used an independent t test or Mann Whitney test with p < 0.05.Results: All participants were men, with an average pure tone audiometry value of 27.50 ± 10.43 dB. Theresults of pure tone audiometry examination found that most participants had normal hearing (58.00%). Thisfinding was inversely proportional to the results of DPOAE examination, in which most participants had“Refer” (78.00%). The mean pure tone audiometry value on participants with DPOAE “Refer” was 20.36 ±3.47 dB and DPOAE “Pass” was 29.51 ± 10.87 dB (p = 0.008). Most participants had “Refer” DPOAE withnormal pure tone audiometry as much as 36.00%, followed by participants with “Refer” DPOAE but mildhearing loss of pure tone audiometry as much as 24.00% (p = 0.002).Conclusion: There is a significant association between pure tone audiometry with DPOAE. Many participantshave normal audiometry but “Refer” DPOAE, and followed by participants experiencing mild hearing losswith “Refer” DPOAE.